An advanced optical metrology view on mixture formation in Diesel sprays - Rieß, Sebastian; Durst, Alexander; Wensing, Michael; Wang, Jin (13th International AVL Symposium on Propulsion Diagnostics, 2018)
An advanced insight into mixture formation in Diesel sprays is deployed utilizing several optical measurement techniques. By means of X-ray imaging, the primary break-up at injection pressures of up to 100 MPa is investigated. Combining measurements of the spray propagation by Mie scattering and Schlieren imaging, the air entrainment process is analyzed against the background of different injection pressures and fuels. These considerations are complemented by measurements of the local mixture composition utilizing Raman spectroscopy. By combination of the applied techniques, it is shown that air entrainment in engine relevant sprays is to a high extent independent from the quality of atomization as long as sufficiently small droplets are provided. Air entrainment is highly dominated by conservation of the initial spray momentum, leading to the admixture of significant amounts of ambient gas into the spray within a short distance to the nozzle exit. The resulting local mixture mass composition and distribution is nearly independent of the fuel’s physical properties and the injection pressure. Differences appear through chemical properties of the fuel such as molar mass and stoichiometric air demand. The choice of a (future) fuel can be fully focused on its chemical properties to achieve desired molar mixtures alongside with an ignition and combustion behavior systematically controlled by a fuel specific chemistr
Keywords: Diesel; Engine; Mixture Formation; Optical Diagnostics